MULTILINGUAL EDUCATION AND INTERFERENCE: WRITTEN UNGRAMMATICAL TAG-SWITCHING AMONG PRE-SERVICE TEACHERS OF ENGLISH LANGUAGE - Oscar Ndayizeye (University of Muhammadiyah Purwokerto, 2016)
This research aims to: (1) show the ungrammaticality of pre-service teachers’ (Bachelor III students’) written tag-switching models and this is disapproving since these subjects are English teachers-to-be. (2) It also tracks tokens of interference of Kirundi, French, Kiswahili and English languages in the Bachelor III students’ written tag-switching examples as a result of the Burundian multilingual education system.The study refers to the observation and Testing as suggested respectively by Cohen et al. (2006) and Hughes (2003). The researcher’s unstructured observation participated in his review of observational data before suggesting any explanation for the phenomena being observed. The test given helped measure on the one hand those pre-service teachers’ achievements of the course objectives and diagnose their strengths and weaknesses on the other hand. The subjects of the study consisted of thirty-six (36) students whose preference was tag-switching in an Exam of Sociolinguistics with the question framed as follows: “Among the different code switching types, choose one and exemplify it with three examples.” The Kuder- Richardson formula 20 (KR-20) and Standard Error Measure (SEM), provided helpful information when having to take decisions about individuals on the basis of their performance in a test such as the one given during this research, (Hughes, ibid:224). The research findings reveal a mismatching between the subjects’ level of study and the written tag-switching examples that they gave: after correction done diligently and skilfully, ungrammaticality is a case and it includes the subjects’ wrong tense use at the tag level and the occurrence of wrong choice of tenses, aspects and mood (either in Kirundi, French and Kiswahili) in the part before tag level. The cause of these erroneous tag- switching examples is revealed to take source in the multilingual education system operational in Burundi. Keywords: Educational multilingualism, interference, tag-switching and ungrammaticality